DISRECTIONARY ACCRUALS DAN PRICE TO BOOK VALUE PERUSAHAAN SUB SEKTOR FOOD AND BEVERAGE - I Gusti Ayu Ratih Permata Dewi (Universitas Triatma Mulya, 2023)
This study aims to obtain empirical evidence about the effect of firm size, profitability, leverage, and liquidity on earnings management. The population in this study are Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The dependent variable in this study is earnings management, while the independent variables in this study are firm size, profitability, leverage and liquidity. In this study using secondary data types. The sample in this study was obtained using a purposive sampling technique which totaled 82 financial statement data and met the requirements as a research sample obtained through the official website of the Indonesia Stock Exchange. The data analysis method used is multiple linear analysis. Based on the research conducted, the results of this study indicate that company size has a positive and not significant effect on earnings management. Profitability and leverage have a negative and insignificant effect on earnings management. Liquidity has a negative and significant effect on earnings management. Earnings management has a negative and significant effect on firm value